Avaliação do desempenho operacional, financeiro e ambiental em uma empresa de transporte ferroviário de cargas - Ribeiro, Fellipe Vitucci de Lucca (2021)
The cargo transport sector is one of the most relevant for the economy and the expectation for the next years is of growth with its performance being fundamental for the competitiveness and positioning of a country in the global market of imports and exports. Talking about Brazil, the country is consolidated in the global commodities market, through the export of primary products, such as agricultural and mineral products, where there is a tendency towards greater use of railways. In this way, it becomes necessary for freight railways to seek an advantageous position in the market with about operational, economic and environmental factors. The brazilian rail freight transport sector strongly depends on non-renewable energy sources with diesel oil being the main fuel used, derived from petroleum and which brings several concerns: polluting gas emissions, high costs and price volatility. In this way, it was not identified in the research carried out in the literature, works that analyzed the operational, financial and environmental performance together in the context of freight rail transport and there are few researches in emerging countries. Thus, the main objective of this work was to understand the effectiveness and contributions provided by actions to improve and solve problems in operational, financial and environmental performance in a freight railway company in the Southeast and Midwest regions of Brazil. The evaluation was carried out through problem mapping and verification of actions for improvement and problem solving, as well as through the analysis of indicators before and after the implementation of the actions. The results showed that the proposed improvement actions reached a satisfactory number of problems, however the analysis of the problems shows that not all problems were prioritized in the same way, missing more actions than those that were carried out. The analysis of the indicators shows an evolution in the operational and environmental performance indices, while the financial performance worsened.